Analisis Strategi Pengembangan Bisnis dengan Pendekatan Analisis Swot Di Nominus Start-Up - Jakadika, Jeulian; Hasbi, Imanuddin (eProceedings of Management, 2024)
Second-hand clothing is currently trending among the public, especially among young people. The interesting thing isthere is an Online Thrift Shop which is one of the trending businesses by selling used clothes online.online. The clothes sold at Online Thrift Shop are clothes that have been worn by someone who is still of high quality and has a unique style.someone who is still of high quality and has its own uniqueness. So that a business idea emergedStartup NoMinus, is a technology-based platform where users can sell and buy new and pre-loved clothes.As for the objectives of this study, among others, are Knowing the SWOT Analysis of Startup No Minus.SWOT Analysis of Start Up No Minus and Formulate a Business Development Strategy for Start Up No Minus.The theory used in this research is Business Model Canvas and SWOT analysis and SWOT Matrix.The method used in this research is descriptive using qualitative analysis. MethodsData collection methods in this study used interviews, observations, documentation, and questionnaires.The results of this study show that the SWOT analysis and SWOT Matrix produce alternative strategies where NoMinus can digitize its business model.NoMinus can digitize by utilizing telecommunications and information technology to expand its business.The results of this alternative strategy become a new foundation where the development strategy is carried out in all building blocks with the followingThe results of the alternative strategy become a new foundation where the development strategy is carried out in all building blocks by implementing a market penetration strategy, development pa